FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR PESERTA DIDIK DI KELAS X SMK NEGERI 3 PADANG - Fenni Fenni (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the presence of students who are less able to adapt to the situation or problem that is being faced, so that it has an impact on their learning achievement. The purpose of this study is to describe: 1) Internal factors that affect student achievement. 2) External factors that affect student achievement. This research uses descriptive quantitative method. The study population was 247 students selected by purposive sampling technique with 45 participants. Based on the research results obtained as follows: 1) Internal factors that affect student achievement are in the low category 2) External factors that affect student achievement are in the low category. The results of this study are recommended for guidance and counseling teachers to develop special programs related to improving student learning achievement so that students can achieve the desired achievement.